2002
DOI: 10.1001/archinte.162.17.1994
|View full text |Cite
|
Sign up to set email alerts
|

Thrombolysis for Acute Stroke in Routine Clinical Practice

Abstract: Protocol deviations occur commonly when thrombolytic therapy is given to stroke patients in routine clinical practice. Patients who receive thrombolysis with major protocol deviations have higher rates of in-hospital mortality and serious extracranial hemorrhage than patients in the NINDS cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
64
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(66 citation statements)
references
References 28 publications
1
64
0
Order By: Relevance
“…23 It is also clear that if patients are not carefully selected, meeting strict inclusion and exclusion criteria, the rate of complications is increased. 24 Thus, as summarized in a practice statement of the American College of Emergency Physicians, ''There is insufficient evidence at this time to endorse the use of intravenous tPA in clinical practice when systems are not in place to ensure that the inclusion/exclusion criteria established by the NINDS guidelines for tPA use in acute stroke are followed.'' 21 When counseling patients and their families about the benefits and risks of IV tPA, one should keep in mind that the NINDS trial demonstrated increased odds of excellent outcomes despite a significant 10-fold increase in the risk of symptomatic intracranial hemorrhage (6.4% vs. 0.6%), and did not alter 30-day mortality.…”
Section: No Blood On the Ct Scan Results Back In <3 Hours From Symptmentioning
confidence: 99%
“…23 It is also clear that if patients are not carefully selected, meeting strict inclusion and exclusion criteria, the rate of complications is increased. 24 Thus, as summarized in a practice statement of the American College of Emergency Physicians, ''There is insufficient evidence at this time to endorse the use of intravenous tPA in clinical practice when systems are not in place to ensure that the inclusion/exclusion criteria established by the NINDS guidelines for tPA use in acute stroke are followed.'' 21 When counseling patients and their families about the benefits and risks of IV tPA, one should keep in mind that the NINDS trial demonstrated increased odds of excellent outcomes despite a significant 10-fold increase in the risk of symptomatic intracranial hemorrhage (6.4% vs. 0.6%), and did not alter 30-day mortality.…”
Section: No Blood On the Ct Scan Results Back In <3 Hours From Symptmentioning
confidence: 99%
“…29) However, the use of rt-PA is restricted to administration within 3 h after onset of symptoms due to the risk of cerebral hemorrhage. 30) Therefore, there are strong clinical demands for neuroprotective agents that can block neuronal death associated with stroke. 31) We have developed DY-9760e, a calmodulin antagonist, which exerts neuroprotective action against cell death induced by Ca 2ϩ overload 15,17) and ameliorates brain injury that occurs after cerebral ischemia in rodents.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the risk of major protocol violations in the administration of alteplase should be noted. In two comprehensive independent communitybased studies, the Cleveland 9 and Connecticut 10 studies (of which only the former was cited in the manufacturer's submission), such violations, most of which appeared to have been accidental, 10 affected 67% of patients receiving alteplase in Connecticut and 50% in the Cleveland area.…”
Section: Summary Of Submitted Clinical Evidencementioning
confidence: 99%